Геоінформаційні системи як інструмент аналізу розселення в контексті впливу на туристичну сферу суспільно-географічного району - Сологуб, Юрій Іванович; Безпала, Ольга Василівна; Харченко, Олена Миколаївна (My University, 2023)
Стаття присвячена аналізу диференціації рівнів сформованості міської системи розселення Столичного суспільно-географічного району як фактора розвитку туристичної сфери. Розкрито сутність міської розселенської мережі Столичного суспільно-географічного району та проведено її структурний аналіз. Виявлено особливості функціонування міської системи розселення суспільно-географічного району, окреслено шляхи її подальшого розвитку. Дослідження системи розселення району проводилося на основі аналізу статистичних індикаторів її функціонування та розвитку з використанням інструментальних можливостей сучасних геоінформаційних систем. Розвиток столиці й Столичного суспільно-географічного району характеризується більш швидкими темпами, що зумовлено наявністю своєрідного каталізатора соціально-економічного життя району, а саме, центрального міста з особливим статусом – Києва

The article is devoted to the analysis of the differentiation of the levels of formation of the urban settlement system of the Capital socio-geographical district as a factor in the development of the tourism sphere of the region. The essence of the urban resettlement network of the Capital socio-geographical district was revealed and its structural analysis was carried out. The peculiarities of the functioning of the urban settlement system of the socio-geographical district are revealed, and the ways of its further development are outlined. The study of the settlement system of the district was conducted on the basis of the analysis of statistical indicators of its functioning and development using the instrumental capabilities of modern geoinformation systems. The city's place in the supporting frame of the settlement system of the socio-geographic district is determined by its belonging to one or another category of centers depending on its socio-economic status. Value orientations of the population, its general standard of living, interests and infrastructure development can be considered the main levers of influence of social factors of formation and development of settlement systems of different taxonomic levels. The strengthening of factors of a social nature of mediated action is noted. Basically, the reasons for this situation are the strengthening of migration processes at the expense of a significant expansion of the sphere of labor activity of the population. In the development of large and medium-sized urban settlements, the secondary sector of the economy is dominant in the initial stages of development, while the tertiary sector prevails in the final stages and is a catalyst for the formation of agglomeration formations. The growing role of the agglomeration component in the settlement system of the Capital socio-geographical district presupposes the development of optimization measures to manage its development. The development of the capital and the Capital socio-geographical district is characterized by a faster pace, which is due to the presence of a peculiar catalyst of the socio-economic life of the district, namely, the central city with a special status - Kyiv. In general, the process of forming the settlement system of the Capital socio-geographical district is closely related to the development of the capital itself and the complication and intensification of relationships between it and other elements of the system
Keywords: кафедра туристичного та готельного бізнесу; Столичний суспільно-географічний район; система розселення; туристична сфера; геоінформаційні системи; Capital socio-geographical district; settlement system; tourist sphere; geoinformation systems